Neuroprotective effect of renin angiotensin system blockers on experimentally induced Alzheimer’s disease in rats - Hewedy, Wafaa A.; El-Hadidy, Wessam F. (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Alzheimer’s disease (AD) is a major world-wide health problem. Much evidence points to a link between hypertension and AD. However, the exact effects of different antihypertensive drugs on AD need to be more assessed. The aim was to evaluate and compare the possible effects of perindopril, and candesartan on cognitive impairment, oxidative stress markers, and brain concentrations of amyloid beta-peptide (Aβ-P) in a rat model of induced dementia. Methods: Thirty-two adult male Wistar rats were distributed among 4 groups; (1) normal controls; (2) rats with dementia induced by intracerebroventricular administration of streptozotocin (ICV-STZ) and received no treatment; (3) ICV-STZ rats treated orally with perindopril for 3 weeks; and (4) ICV-STZ rats treated orally with candesartan for 3 weeks. The assessed parameters were spatial memory by Morris Water Maze test, brain tissue level of total antioxidant capacity (TAC), reduced glutathione (GSH), lipid peroxidation product (malondialdehyde [MDA]), and Aβ-P. Results: Both perindopril and candesartan attenuated STZ-induced memory impairment, caused a significant increase in TAC and GSH levels, reduced MDA levels, whereas only candesartan significantly reduced Aβ-P levels. Conclusions: This study reports that candesartan and perindopril can reverse the free radical induced damages and resultant memory defects, and may suggest candesartan as worthy drugs for prevention of Aβ-P deposition in this animal model of AD.